Ornate Dvarashakha (door jamb) of the Mandaleshwar Mahadev Temple - Temples of India Project Team (Jio Institute, 2024)
The entrance of the garbhagriha (sanctum sanctorum) of the Mandaleshwar Mahadev Temple is marked by an ornate dvarashakha (door jamb). The pedya (lower section of the dvarashakha) has depictions of dvarapalas (door guardians) and river goddesses. The dvarashakha has an attached chandrashila (moon stone) motif on the floor.